Mechanics-Based Failure Model of Tube Hydro-Bulging Test - Di, Bozhou; Liu, Heli; Dhawan, Saksham; Wang, Kehuan; Liu, Xiaochuan; Politis, Denis J. (Frontiers in Mechanical Engineering, 2022)
Tube hydroforming has been widely applied by the automotive sector to produce hollow parts. As a popular tube hydroforming test method, tube hydro-bulging needs an analytical failure model to analyse the formability of tubular materials. In the present work, a failure prediction model has been developed to predict the bulging height limit (BHL) of the hydro-bulging test. The model utilised the Hill’s orthogonal anisotropic model to characterise the tube material, a geometry model to characterise non-loading path and the M-K model to predict failure. Defects in multiple directions were taken into consideration. The developed model was applied on two tubes of different materials as case studies to verify its validity. It is shown that the developed model is capable of predicting the forming limit or determining the imperfection factor of tubular materials.